2023
DOI: 10.2308/tar-2021-0013
|View full text |Cite
|
Sign up to set email alerts
|

The Disclosure and Consequences of U.S. Critical Audit Matters

Abstract: This study uses difference-in-difference analyses to examine the consequences of adopting the U.S. critical audit matter (CAM) disclosure requirement for preparers and users of financial reports. The CAM requirement is one of the largest expansions of the U.S. audit report since the 1940s. We document significant changes to financial statement footnotes referenced by CAMs, which suggests an indirect consequence where management disclosure changes in areas that are expected to be scrutinized following auditor-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
46
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(48 citation statements)
references
References 48 publications
2
46
0
Order By: Relevance
“…In 2017, the Public Company Accounting Oversight Board set standards for communicating critical audit matters (CAMs), which are similar to KAMs. Burke et al (2022) found that communicating CAMs does not provide incremental information for the market in the United States. These results indicate that the information value of KAMs/CAMs is limited in the developed markets.…”
Section: Background and Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2017, the Public Company Accounting Oversight Board set standards for communicating critical audit matters (CAMs), which are similar to KAMs. Burke et al (2022) found that communicating CAMs does not provide incremental information for the market in the United States. These results indicate that the information value of KAMs/CAMs is limited in the developed markets.…”
Section: Background and Literature Reviewmentioning
confidence: 99%
“…These scholars also focused on the impact of communicating KAMs on the quality of financial statements and audits quality. Most scholars did not find evidence that communicating KAMs/CAMs affects audit quality and the quality of financial statements (Bédard et al, 2016; Burke et al, 2022; Gutierrez et al, 2018; Liao et al, 2022). Only Reid et al (2019) discovered that communicating KAMs is associated with an improvement in the quality of financial statements.…”
Section: Background and Literature Reviewmentioning
confidence: 99%
“…They find a positive relationship between the number of items and risk-related words in auditor and management disclosures, which relationship is strengthened in firms with audit committees. Burke et al (2022) study the changes in financial statement footnote disclosures following auditors referencing footnote disclosures in their CAMs. They conclude that heightened auditor interest in the footnote disclosures prompts management changes to those disclosures.…”
Section: Prior Researchmentioning
confidence: 99%
“…In a US context, Burke et al. (2022, p. 1–2) acknowledge that differences in regulatory, capital markets and legal environments could lead to differences in implementing expanded audit report requirements.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation